Coccidiosis in Murrah Buffalo Calves from Meghalaya’s Subtropical Hilly Region - Das, Meena; Kumar, Rakesh; Katiyar, Rahul (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study reports the prevalence of coccidiosis in Murrah buffalo calves (8 nos.) of 11-22 days of age in hilly region of Meghalaya. Clinical signs observed were diarrhea, anorexia, weakness and loss of weight. Fecal sample examination by flotation and modified McMaster techniques revealed the presence of four species of Eimeria, viz., E. bareillyi (29.42%), E. zuernii (22.76%), E. bovis (36.53%) and E. ellipsoidalis (11.29%). High intensity of infection oocyst per gram (OPG) of feces was observed in infected calves. The OPG ranged from 20200 to 121000. Mortality observed when OPG exceeded 121000 which may be due to severe diarrhea, anorexia and weakness. The calves were successfully treated with Amprolium @ 10 mg per kg body weight orally for 7 days, Ceftriaxone @ 0.5 gm I/M for 5 days, Melonex @ 1.5 mL I/M for 5 days, Tribivet @ 1.5 mL I/M along with vimeral @ 10 mL orally for 3 days and fluid therapy @ 500 mL intravenously daily for 3 days. After 7 days of treatment most of the calves recovered gradually and started normal feeding.